Sounds of modern history: auditory cultures in 19th and 20th century europe - Morat, Daniel (Berghahn Books, 2014)
Long ignored by scholars in the humanities, sound has just begun to take its place as an important object of study in the last few years. Since the late 19th century, there has been a paradigmatic shift in auditory cultures and practices in European societies. This change was brought about by modern phenomena such as urbanization, industrialization and mechanization, the rise of modern sciences, and of course the emergence of new sound recording and transmission media. This book contributes to our understanding of modern European history through the lens of sound by examining diverse subjects such as performed and recorded music, auditory technologies like the telephone and stethoscope, and the ambient noise of the city.